Efek Imunomodulator Polisakarida Rimpang Temu Putih [Curcuma zedoaria(Christm.) Roscoe)] - MEUTIA FARADILLA; MARIA IMMACULATA IWO (Fakultas Farmasi Universitas Pancasila, 2014)
Polysaccharide from white turmeric [Curcuma zedoaria (Christm.) Roscoe)] rhizome has been found to have anti-tumor activity against sarcoma 180 cells and able to increase macrophage activity in vitro. Since the modulation of immune system also plays a role in eliminating tumor cell, this study was aimed to determine the immunomodulatory effect of C. zedoaria polysaccharide.Immunomodulatory activity of the polysaccharide fraction was studied in Swiss Webster mice through determination of phagocytic index from reticuloendothelial system, total antibody titers, delayed type hypersensitivity (DTH) reaction and splenocyte proliferation assay. Based on the carbon clearance test, polysaccharide fraction at dose 300 mg/kg bw has higher phagocytic index (1.34) which means it has immunostimulatory activity. At the same dose, polysaccharide fraction enhance humoral immune response shown by primary and secondary antibody titers (1:128 and 1:4096) higher than control. This dose also stimulated delayed type hypersensitivity reactions by 19.41% respectively. In splenocyte proliferation assay, polysaccharide fraction of C. zedoaria was significantly stimulated splenocyte proliferation at contentration 10-6 to 1 mg/mL (p < 0.01). Based on those results, polysaccharide fraction of C. zedoaria at dose 300 mg/kg bw has potency to be developed as immunomodulator.